QUALITY AND RISK ASSESSMENT OF COFFEE SENNA (SENNA OCCIDENTALIS) AND ITS ASSOCIATED SOIL FROM GARUJE POLLUTED SITE IN DANMAGAJI ZARIA, KADUNA STATE, NIGERIA - Uba, Sani; Usman, Bilyaminu Muhammad; Abubakar, Sani; Fanika, Suleiman (FUDMA JOURNAL OF SCIENCES, 2025)
This study evaluates the levels of selected heavy metal contents in soil and coffee senna samples and the risk associated with their consumption, if polluted. Samples of leaves, roots, seeds, and soils were collected at L1, S1, R1, SL1, L2, S2, R2, SL2 (both polluted and control sites). Plant root, leaves and seed collected were washed with distilled water to remove attached soil particles, the root was cut into a smaller portions and then placed in a large crucible where it was dried to 100 oC for 48 hours to remove moisture. Soil samples were collected at a depth of 0 – 5 cm and then dried to remove moisture, followed by sieving to remove debris the size of the mesh used was 2 mm. the samples were analysed for arsenic (As), cadmium (Cd), mercury (Hg), nickel (Ni), and lead (Pb) concentrations using A.A.S and risk assessments was conducted using EDI (estimated daily intake), HQ (hazard quotients), and TEQ (toxic equivalent quotient) metrics. The heavy metal contents in the leaves, root, soil and seed of the analysed samples were in the ranges of arsenic (As): 0.02 ± 0.01mg/kg (R1, S1) to 0.26±0.07 mg/kg (L2), cadmium (Cd): 0.12 ± 0.03 mg/kg (R1) to 0.73 ± 0.21 mg/kg (SL2), mercury (Hg): 0.08 ± 0.02 mg/kg (L1) to 1.03 ± 0.30 mg/kg (R2), Nickel (Ni) 0.01 ± 0.00 mg/kg (SL1) to 0.41 ± 0.12 mg/kg (SL2) while a range of 0.05 ± 0.02 mg/kg (L1) to 11.59 ± 3.35 mg/kg (SL2) was recorded...